2021
DOI: 10.1038/s41531-020-00151-w
|View full text |Cite|
|
Sign up to set email alerts
|

Pallidal stimulation as treatment for camptocormia in Parkinson’s disease

Abstract: Camptocormia is a common and often debilitating postural deformity in Parkinson’s disease (PD). Few treatments are currently effective. Deep brain stimulation (DBS) of the globus pallidus internus (GPi) shows potential in treating camptocormia, but evidence remains limited to case reports. We herein investigate the effect of GPi-DBS for treating camptocormia in a retrospective PD cohort. Thirty-six consecutive PD patients who underwent GPi-DBS were reviewed. The total and upper camptocormia angles (TCC and UCC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 37 publications
0
17
0
Order By: Relevance
“…There is also an argument over the effectiveness of DBS in the STN vs. Globus Pallidus internus (GPi). In a case study of two patients with near crippling camptocormia (a trunk flexion exceeding 30° [ 39 ]), GPi DBS completely reversed the camptocormia and restored posture to normal [ 40 ]. Furthermore, in a small study of three patients with PD, two with bilateral DBS in the STN and one with bilateral GPi DBS, no or mild improvement of trunk flexion was seen in the two patients with DBS in the STN but a moderate improvement was seen in the patient with GPi DBS [ 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…There is also an argument over the effectiveness of DBS in the STN vs. Globus Pallidus internus (GPi). In a case study of two patients with near crippling camptocormia (a trunk flexion exceeding 30° [ 39 ]), GPi DBS completely reversed the camptocormia and restored posture to normal [ 40 ]. Furthermore, in a small study of three patients with PD, two with bilateral DBS in the STN and one with bilateral GPi DBS, no or mild improvement of trunk flexion was seen in the two patients with DBS in the STN but a moderate improvement was seen in the patient with GPi DBS [ 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…The included studies have been conducted between 2003 and 2021. Regarding study designs, nine case reports [ 5 , 13 , 17 – 20 , 23 , 25 , 28 ] (i.e., 50%), four case series [ 14 , 16 , 22 , 26 ] (i.e., 22.2%), three retrospective observational cohort studies [ 21 , 24 , 30 ] (i.e., 16.6%), one review article including two reported cases [ 27 ] (i.e., 5.6%), and one prospective trial [ 29 ] (i.e., 5.6%) were assessed. Fifteen studies [ 13 , 14 , 16 21 , 25 , 27 30 , 32 ] reported follow-up data with a mean follow-up time of 21.5 months (range 5–67 months).…”
Section: Resultsmentioning
confidence: 99%
“…(1) Five studies reported clinical outcomes by standardized scores (i.e., Visual Analogue Scale [VAS] [ 16 , 24 ], Burke-Fahn-Mardsen Dystonia Rating Scale |BFM-RS] [ 16 , 17 ], S-LANNS Score [ 17 ], Schwab-England activity of daily living scale [S-E] [ 29 ], and special consideration of Unified Disease Parkinson Rating Scale [UPDRS]-III item 28 score [ 26 ]), four studies anecdotally reported the clinical outcome without standardizes scores [ 13 , 18 , 19 , 27 ], and nine studies did not take the clinical course into account. (2) Changes of the sagittal thoraco-lumbar angle (TLA) (or shoulder-hip knee and head-shoulder-hip angle) assessed by photographs were assessed in 13 (i.e., 72,2%) studies [ 5 , 14 , 17 , 19 25 , 28 30 ], with outcome parameter either defined as improvement in case of > 50% relative reduction of the TLA or as absolute value < 30° of the TLA at last follow-up (Table 1 ). Two studies further distinguished improvement as effective and partially effective: in Sakai et al, partially effective was defined when the TLA became < 30° after DBS but did not last for > 6 months [ 21 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations